2019
DOI: 10.3746/pnf.2019.24.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pectin on the Expression of Proteins Associated with Mitochondrial Biogenesis and Cell Senescence in HT29-Human Colorectal Adenocarcinoma Cells

Abstract: Mitochondria dynamic is regulated by different proteins, maintaining a balance between fission and fusion. An imbalance towards mitochondrial fission has been associated with tumor cell proliferation. The aim of this study was to analyze whether pectin modifies the viability of human colon cancer cells and the expression of proteins involved in mitochondrial fusion and fission. The human colon carcinoma cell line HT29 cells was growth in 10% fetal bovine serum in the absence and presence of pectin. Pectin redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Senescent cells are characterized by biochemical and morphological changes such as flattening and/or nuclear enlargement (508). There are several classical biomarkers of cellular senescence and they comprise: senescence-associated beta-galactosidase (SA-ß-gal) activity, expression of p53 protein, the amount of p53 in the nucleus, increase in expression of p14 (Arf), p16 (Ink4a) and p21 (Waf1), SASP, and often senescenceassociated heterochromatic foci (SAHF) (12,505,507,(509)(510)(511)(512)(513)(514)(515). Furthermore, senescent cells display low Ki67 levels and show levels of heterochromatin protein 1 (HP1) gamma ( 516), as well as di-or tri-methylated lysine 9 of histone H3 (H3K9Me2/3) and histone H2A variant (macroH2A) (505,517,518).…”
Section: Therapy-induced Senescence: Its Hallmarks Biomarkers and Its Role In Csc Generationmentioning
confidence: 99%
“…Senescent cells are characterized by biochemical and morphological changes such as flattening and/or nuclear enlargement (508). There are several classical biomarkers of cellular senescence and they comprise: senescence-associated beta-galactosidase (SA-ß-gal) activity, expression of p53 protein, the amount of p53 in the nucleus, increase in expression of p14 (Arf), p16 (Ink4a) and p21 (Waf1), SASP, and often senescenceassociated heterochromatic foci (SAHF) (12,505,507,(509)(510)(511)(512)(513)(514)(515). Furthermore, senescent cells display low Ki67 levels and show levels of heterochromatin protein 1 (HP1) gamma ( 516), as well as di-or tri-methylated lysine 9 of histone H3 (H3K9Me2/3) and histone H2A variant (macroH2A) (505,517,518).…”
Section: Therapy-induced Senescence: Its Hallmarks Biomarkers and Its Role In Csc Generationmentioning
confidence: 99%
“…Abnormal mitochondrial morphology was likewise found in senescent cells with altered expression profiles of molecules such as MFN1, MFN2, and OPA1 (Crane et al 2010 ; Marzetti et al 2017 ). Futhermore, the relevance of mitochondrial dynamics to ischemic diseases (Yu et al 2020 ; Maneechote et al 2019 ; Guan et al 2019 ), renal diseases (Zhong et al 2021 ; Chen et al 2020b ), immune-related diseases (Mills et al 2017 ; Banoth and Cassel 2018 ) and cancer (Porporato et al 2018 ; Zamorano-León et al 2019 ), among others, has been studied.In addition, the mechanism of the treatment through mitochondrial pathway for related diseases may become a popular topic in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of the MTT test revealed that the polymers mixture without L. rhamnosus inhibited Caco-2 cell line growth, it had a minor effect on apoptotic and anti-apoptotic genes. It has been reported that pectin was unable to affect the expression of Bcl-2 or caspase-3 activity in HT29 cells (61) . In JAPS, 1(1), 2024 44 ISSN: 3009-7061 addition, Ramirez-Rico et al documented that the expression of antiapoptotic protein for caspase-3 and Bcl-2 in intestinal lymphocytes was unaffected upon treatment with whey protein (68) .…”
Section: Anti-proliferative Activity Of a Mixturementioning
confidence: 94%
“…5. In 2019, Zamorano et al and his team (61) studied the influence of pectin on colon cancer cells. In this study, the viability of HT29 cells was reduced by pectin in a concentration-dependent manner.…”
Section: Anti-proliferative Activity Of a Mixturementioning
confidence: 99%